Clinical validation of the Virtual Reality Functional Capacity Assessment Test – Short List (VRFCAT‐SLx) for assessment of iADL functioning in early symptomatic Dementia: Sensitivity to cognitive and functional change over time. (20th December 2022) - Schoemaker, Dorothee; Atkins, Alexandra S; Abraham, Chelsea; Flanagan, Chloe; Evans, Haley; Madsen, Corrine; Sickel, Nancy; Stevens, Heather; Amaya, Alexandra C; Plassman, Brenda L; Loewenstein, David; Welsh‐Bohmer, Kathleen A.; et al.
Abstract: Background: Assessment of functional capacity is critical to the diagnosis and monitoring of Alzheimer's disease and related dementias. The VRFCAT (Keefe et al., 2016) is a performance‐based assessment of iADL functioning that is completed on a tablet. Previous work on the VRFCAT has demonstrated correlations with clinical endpoints and sensitivity to cognitive impairment in individuals with subjective cognitive decline (SCD) and schizophrenia. To facilitate use longitudinally and in more impaired patient groups, the VRFCAT "short list" (VRFCAT‐SLx) was recently developed to reduce task complexity and length (see Atkins et al. AAIC submission). The aim of the present work was to characterize the VRFCAT‐SLx's sensitivity to longitudinal clinical changes in subjects with early symptomatic MCI/AD dementia Method: At the time of submission, participants included 77 adults (32 male; mean baseline? age = 73.29, SD = 7.52) with clinical diagnoses of MCI/AD and CDR global scores of 0.5 or 1.0. Participants completed the VRFCAT‐SLx and other established measures (i.e., ADCS‐ADL‐MCI, MMSE, CDR, BAC cognitive tests) at Baseline and Follow‐up. At submission, 22 participants had completed both visits (mean follow‐up interval ± SD: 13 ± 4.8 months). We evaluated VRFCAT‐SLx performance as a predictor of cognitive and functional change over time, and examined relationships between longitudinal change on the VRFCAT‐SLx, MMSE, ADCS‐ADL‐MCI, and CDR‐SB. Result: Baseline VRFCAT‐SLx performance predicted decline on both the CDR Sum of Boxes (β = 0.44, p<0.05) and MMSE Total score (β = ‐0.48, p = 0.01), even when controlling for baseline performance, age, and length of follow‐up interval. Additionally, increases in the VRFCAT‐SLx Total Adjusted Time (i.e., worsening performance) at follow‐up was significantly correlated with observed decline on the MMSE (r = ‐0.55, p<0.01), CDR‐SB (r = 0.59, p<0.01), and ADCS‐ADL‐MCI (r = 0.44, p<0.05). These associations remained significant after adjusting for age and length of follow‐up interval. Conclusion: Longitudinal results indicate that performance on the VRFCAT‐SLx reliably predicts and tracks cognitive and functional change in early symptomatic dementia. These findings support the validity of the VRFCAT‐SLx as a sensitive assessment of iADL functioning in MCI/AD dementia.